Visual Detection of SARS-CoV-2 RNA by Conventional PCR-Induced Generation of DNAzyme Sensor - Anantharaj, Anbalagan; Das, Soon Jyoti; Sharanabasava, Patil; Lodha, Rakesh; Kabra, Sushil K.; Sharma, Tarun Kumar; Medigeshi, Guruprasad R. (Frontiers in Molecular Biosciences, 2020)
The gold standard for diagnosis of SARS-CoV-2, the causative agent of COVID-19, is real-time PCR which is labour-intensive, expensive and not widely available in resource-poor settings. Therefore, it is imperative to develop novel, accurate, affordable and easily accessible assays/sensors to diagnose and isolate COVID-19 cases. To address this unmet need, we utilized the catalytic potential of peroxidase like DNAzyme and developed a simple visual detection assay for SARS-CoV-2 RNA using a conventional thermal cycler by the polymerase chain reaction (PCR)-induced generation of DNAzyme sensor. The performance of RT-PCR DNAzyme-based sensor was comparable to that of real-time PCR. The pilot scale validation of RT-PCR DNAzyme-based sensor has shown ~100% sensitivity and specificity in clinical specimens (nasopharyngeal swab, n=34) with a good correlation (Spearman r = 0.799) with Ct-value of fluorescence probe-based real-time PCR. These findings clearly indicate the potential of this inexpensive, sensitive and specific molecular diagnostic test to extend our testing capabilities for the detection of SARS-CoV-2 to curtail COVID-19 transmission.